Note—Author's Reply to Graves' Note on the Paper “Critical Ratio Scheduling: An Experimental Analysis” - Berry, William L. (Management Science, 1977)
Author's Reply to Graves' Note on the Paper (Berry, W. L., V. Rao. 1975. Critical ratio scheduling: an experimental analysis. Management Sci. 22 (2, October) 192–201).